A new perspective on talent management: An integrative review of the current literature - Kiriakos Tsaousiotis; Konstantinos Panitsidis; Konstantinos Spinthiropoulos; Eleni Zafeiriou (Administrative Sciences, 2025)
Purpose: Although talent management is widely applied across various business sectors, the comprehensive literature focusing on talent management within the context of migration flows remains limited. This paper addresses this gap by conducting an extensive review of the studies published between 2018 and 2023, with particular attention given to the absence of talent management frameworks tailored to refugees. By synthesizing the existing literature, this study aims to highlight the areas where talent management practices can be developed to better address the unique challenges faced by migrant populations. Methodology: This research utilizes the PRISMA methodology and VOSviewer for bibliometric analysis. A total of 62 studies were included, providing insights into the role of talent management across different contexts. Analysis categorizes the studies by the research field, the keywords, the methods, the statistical measures, the geographic origin (countries/universities), and the publication year. Findings: Analysis revealed distinct categorization criteria, including the research field, the keywords, the methodologies, the statistical approaches, the country of origin, and the publication year. This study also identified critical research gaps, particularly in talent management practices related to refugee populations. These findings point to future research directions, emphasizing the need to develop talent management frameworks that can address migration-related challenges. Originality/value: This literature review is innovative due to its cross-disciplinary examination of the talent management literature, focusing on a previously unexplored intersection between talent management and migration. To the best of the authors' knowledge, this is the first study to systematically analyze the gap in migration-related talent management, underscoring the need for further research in this important and emerging field.
Keywords: 350; migration management; refugee employment; refugee management; talent; talent development; talent management; talent migration; talent refugees; talent strategies